NEW WORD FORMATION PROCESS IN GENERATION Z’S ONLINE DISCOURSE: A CASE STUDY OF ANDREA NICOLE’S SOCIAL MEDIA - Salma Puan Iqrina; Dohra Fitrisia; Kismullah Abdul Muthalib (LinguAmerta, 2026)
Nowadays, technology has developed significantly. There are significant changes in language and the spread of new languages on social media. This research aims to identify and classify the types of new word formation processes used in Generation Z’s online language on Andrea Nicole’s social media. This qualitative study obtained the data from two social media platforms: Instagram and TikTok. The data were collected through observation and by capturing users’ written language that went through the six types of word formation processes proposed by Yule (2014), found on the social media accounts of Andrea Nicole on Instagram and TikTok, in posts, captions, and her followers’ comment sections, from January-June 2025. This study identified 44 words indicating word formation that often occur on social media today and classified them into six categories: borrowing, compounding, clipping, derivation, acronyms, and multiple processes. Based on the analysis, seven borrowing words, five compounding words, ten clipping words, six derivation words, ten acronym words, and six words formed through multiple processes were found. The words found are often used by many people today. This study provides insight into the widely used process of word formation, especially among younger generations such as Generation Z.